Overlapping distribution of K(ATP) channel-forming Kir6.2 subunit and the sulfonylurea receptor SUR1 in rodent brain. - Karschin, C; Ecke, C; Ashcroft, F; Karschin, A (1997)
ATP-sensitive K+ channels comprise a complex of at least two proteins: a member of the inwardly rectifying Kir6 family (e.g. Kir6.2) and a sulphonylurea receptor (e.g. SUR1) which belongs to the ATP-binding cassette (ABC) superfamily. Using specific radiolabeled antisense oligonucleotides, the cellular localization of both mRNAs was investigated in the rodent brain by in situ hybridization. The distribution of both transcripts was widespread throughout the brain and showed a high degree of overlap with peak expression levels in the hippocampus, neocortex, olfactory bulb, cerebellum, and several distinct nuclei of the midbrain and brainstem, indicating their important role in vital brain function.